Organizational Commitment, Competence on Job Satisfaction and Lecturer Performance: Social Learning Theory Approach - Amin, Muh. Sirojuddin (Manunggal Halim Jaya, 2022)
The purpose of this study is to measure employee performance seen from the achievement of lecurer work. Furthermore, the research design is structured in such a way that the researcher obtains answers to the research questions. The research sample is 244 lecturer in Indonesia, data collection with online survey. The results showed that organizational commitment had a significant positive effect on job satisfaction. Feel happy, think, emotionally attached, worry, sense of belonging, little choice, alternative, sacrifice, loyal, obligation, loyal, work, one organization, wise, and make a very strong contribution. Competence directly has a significant positive effect on employee job satisfaction. This means that through the competencies possessed by lecturer Competence directly has a significant positive effect on employee performance. Competencies possessed by lecturer give a real meaning to employee performance. Job satisfaction directly has a significant positive effect on employee performance. Organizational commitment indirectly has a positive and insignificant effect on performance through job satisfaction. Competence indirectly has a significant positive effect on performance through job satisfaction.